PENGARUH UKURAN PERUSAHAAN, SISTEM PENGENDALIAN INTERNAL, DAN LEVERAGE TERHADAP AUDIT DELAY (Studi pada Perusahaan Jasa Transportasi yang Terdaftar di Bursa Efek Indonesia Tahun 2014 - 2017) - Haryani, Titik; Rispantyo, Rispantyo; Puji Astuti, Dewi Saptantinah (Universitas Slamet Riyadi, 2019)
Timeliness of accounting information publication can be affected by short and long audit delay. Some of the factors that may affect the length of audit delay are company size, internal control system and leverage. This research is testing the significance of the influence of the size of the company, internal control systems, and leverage against the audit delay. This research was conducted on the transportation services company listed on the Indonesia stock exchange during the years 2014 - 2017. With a purposive sampling method sampling and retrieved samples of as many as 28 companies from 45 companies. This research is using double linear regression technique. The results showed that company size variable has no significant effect on audit delay variable, internal control system variable significant negatif effect on audit delay variable, and leverage variable has no significant effect on audit delay variable.